Modern Electron Microscopy in Physical and Life Sciences - Janecek, Milos; Kral, Robert (IntechOpen, 2016)
This book brings a broad review of recent global developments in theory, instrumentation, and practical applications of electron microscopy. It was created by 13 contributions from experts in different fields of electron microscopy and technology from over 20 research institutes worldwide.